2021
DOI: 10.3389/feart.2020.598839
|View full text |Cite
|
Sign up to set email alerts
|

New High-Resolution Modeling of the 2018 Palu Tsunami, Based on Supershear Earthquake Mechanisms and Mapped Coastal Landslides, Supports a Dual Source

Abstract: The Mw 7.5 earthquake that struck Central Sulawesi, Indonesia, on September 28, 2018, was rapidly followed by coastal landslides and destructive tsunami waves within Palu Bay. Here, we present new tsunami modeling that supports a dual source mechanism from the supershear strike-slip earthquake and coastal landslides. Up until now the tsunami mechanism: earthquake, coastal landslides, or a combination of both, has remained controversial, because published research has been inconclusive; with some studies explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 62 publications
3
30
0
Order By: Relevance
“…Moreover, this study found 3 submarine mass failures with a total size of ~0.05 km 3 in the mentioned area. By followingNakata et al (2020),Schambach et al (2021) modeled submarine mass failure with a size of ~0.026 km 3 in a similar area and found good agreement with the nearby observed runups (Fig.6, yellow ellipse). According to these resulting landslides, this study strongly emphasizes the potential submarine landslides in Lower Palu Bay.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…Moreover, this study found 3 submarine mass failures with a total size of ~0.05 km 3 in the mentioned area. By followingNakata et al (2020),Schambach et al (2021) modeled submarine mass failure with a size of ~0.026 km 3 in a similar area and found good agreement with the nearby observed runups (Fig.6, yellow ellipse). According to these resulting landslides, this study strongly emphasizes the potential submarine landslides in Lower Palu Bay.…”
supporting
confidence: 67%
“…Various modeling efforts have been carried out to 60 simulate tsunami propagation using the COMCOT model (Heidarzadeh et al 2019;Carvajal et al, 2019;Gusman et al 2019;Liu et al, 2020;Sepúlveda et al, 2020). In more recent works, several studies have been performed to simulate landslideinduced tsunamis using other uncoupled methods, in which the landslide mass and tsunami propagation are separately calculated (Nakata et al, 2020, Paris et al, 2020Ulrich et al 2019;Schambach et al, 2021). Some previous works have successfully acquired agreeable results by comparing the surveyed runup heights to the inundation 65 depths, the recorded water levels at the Pantoloan tide gauge, or video-inferred waveforms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indian Ocean [30] and for the 2011 Tohoku coseismic tsunamis [31], and for the 2018 Palu tsunami [47].…”
Section: Tsunami Propagation Modelmentioning
confidence: 99%
“…Tsunami simulations are performed for the 18 selected coseismic sources using the fully nonlinear and dispersive Boussinesq model FUNWAVE-TVD [61,50,31], by one-way coupling in a series of nested spherical or Cartesian coordinate grids. FUNWAVE has been validated for a collection of tsunami benchmarks [53,29], and used in the simulation of many historical [60,22,30,51,24,31,52,21,26,46,47] and hypothetical [23,1,25,54,49,27,45] tsunami case studies. As we only aim at assessing the global coastal tsunami hazard caused by the selected sources along the USEC, we only use two levels of nested grids (Fig.…”
Section: Introductionmentioning
confidence: 99%